MODEL NEGARA DALAM ISLAM: TINJAUAN TAFSĪR MAQĀṢIDĪ - Lufaefi Lufaefi (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
The Islamic study who until now still raises the pro-cons is about the state model. Sayyid Quṭb, Taqī al-Din al-Nabhāni and Abū A‘lā Al-Maudūdī, are scientists who conclude that Islam has a state model, namely khilāfah islāmiyyah. This first group closes the space for possible state models other than khilāfah islāmiyyah. Until often this idea raises acts of terrorism and anarchism. While in other groups, such as ‘Alī‘ Abd Rāziq, Nurcholis Madjid and Gus Dur are a series voicing their ideas that Islam does not have a particular state model. This article to find the nature of the state model in Islam. The approach used is the interpretation approach maqāṣidi Ṭāhir Ibn ‘Āsyūr. As a result, the Islamic state model in the Koran is the state provided that it meets the principles of the state according to Islam, such as justice, deliberation, charity, social security, peace, security and equality. Whatever country model, as long as it still holds the six principles above, then the essence is the model of an Islamic state.